8 State Space Model
8 State Space Model
T.Kaputu
Introduction
These resources look at a state-space models their origins,
properties and use in control
The first few resources focus on origins.
𝐵
Mass 𝑓𝑎 (𝑡) M 𝑓𝑎 (𝑡)
𝐵 𝑀
𝑑𝑑 𝐵 1
= − 𝑣+ 𝑓⇒ 𝑣̇ = 𝐴𝐴 + 𝐵𝐵
𝑑𝑑 𝑀 𝑀 State derivative is linear
in the state and the input
Resistor-Capacitor in series
Consider the following circuit and use Kirchhoff’s voltage law to
derive an appropriate model
𝑹𝟏 𝑑𝑑
𝑣1 = 𝑖𝑖1 = 𝑅1
𝑑𝑑
𝒗𝟏
𝑪 1
𝒗𝟐 𝑣2 = 𝑞
𝐶
𝑞
𝑣𝑖𝑖 = 𝑣1 + 𝑣2 = 𝑅1 𝑞̇ +
𝐶
Defining State derivatives
𝑑𝑑 1 𝐾
𝑇 + 𝑥 = 𝐾𝐾 ⇒ 𝑥̇ = − 𝑥 + 𝑢
𝑑𝑑 𝑇 𝑇
𝑥̇ = 𝐴𝐴 + 𝐵𝐵 A B
State of a 2nd order ODE
𝑥̇ = 𝑣
𝒗𝑳 𝒗𝑹
𝒗𝑪
𝒗(𝒕)
𝑑𝑑 𝑑𝑑 1 𝑑𝑑 1 𝑑𝑑 1
𝐿 =𝑣 𝑡 −𝑅 + 𝑞 ⇒ = 𝑣 𝑡 −𝑅 + 𝑞
𝑑𝑑 𝑑𝑑 𝐶 𝑑𝑑 𝐿 𝑑𝑑 𝐶
𝑑𝑑
=𝑖
𝑑𝑑
𝑖̇ −𝑅/𝐿 −1/𝐿𝐿 𝑖 1/𝐿
= + 𝑣
𝑞̇ 1 0 𝑞 0
𝒛̇ 𝒛 𝑩
𝑨
Pendulum
• A pendulum of length 𝑙 with end mass 𝑚 is able to swing freely
(assume some friction-constant 𝑘)
• A model can be derived using force balance in the tangential
direction (small angles)
• Choose states:
𝜃 𝑎𝑎𝑎 𝜃̇ = 𝑤 𝒎𝒎𝒎𝒎 − 𝒎
Pendulum state spacemodel
State derivatives: 𝑚𝑚𝜃̈ = −𝑚𝑚𝜃 − 𝑘𝑘𝜃̇
• from the equation, we know that
𝜃̈ = 𝑤̇ 𝑎𝑎𝑎 𝜃̇ = 𝑤
1
𝑤̇ = −𝑚𝑚𝜃 − 𝑘𝑘𝑘
𝑚
𝑤̇ −𝑘𝑘/𝑚𝑚 −𝑚𝑚/𝑚𝑚 𝑤 0
̇ = + 𝑓
𝜃 1 0 𝜃 0
State space models from a generic ODE
𝑑𝑑1 𝑑𝑑
𝑎 + 𝑏𝑥1 + 𝑐𝑐 = 𝑘𝑘 𝑥1 =
𝑑𝑑 𝑑𝑑
𝑑 𝑥1 −𝑏/𝑎 −𝑐/𝑎 𝑥1 𝑘
= + 𝑢
𝑑𝑑 𝑥 1 0 𝑥 0
Consider a generic nth order ODE
The main technique is to treat every derivative in the ODE
as 1st order derivative, that is the first derivative of some
state, to be defined.
Already a first
The definition of the states is then automatic derivative of x
𝑑𝑛 𝑥 𝑑 𝑛−1 𝑥 𝑑2𝑥 𝑑𝑑
𝑎𝑛 𝑛 + 𝑎𝑛−1 𝑛−1 + ⋯ + 𝑎2 2 + 𝑎1 + 𝑎0 𝑥 = 𝑘𝑘
𝑑𝑡 𝑑𝑡 𝑑𝑡 𝑑𝑑
𝑑 𝑛−1 𝑥
This is the derivative of . This is the derivative of
𝑑𝑡 𝑛−1
𝑑 𝑛−1 𝑥 dx/dt. Let dx/dt=𝑥1
let = 𝑥𝑛−1
𝑑𝑡 𝑛−1
Consider a generic nth order ODE
𝑑 𝑛−1 𝑥 𝑑𝑥𝑛−2 𝑑 2 𝑥 𝑑𝑥1 𝑑𝑑
𝑥𝑛−1 = 𝑛−1 = 𝑥2 = 2 = 𝑥1 =
𝑑𝑡 𝑑𝑑 𝑑𝑡 𝑑𝑑 𝑑𝑑
𝑑𝑛 𝑥 𝑑 𝑛−1 𝑥 𝑑2𝑥 𝑑𝑑
𝑎𝑛 𝑛 + 𝑎𝑛−1 𝑛−1 + ⋯ + 𝑎2 2 + 𝑎1 + 𝑎0 𝑥 = 𝑘𝑘
𝑑𝑡 𝑑𝑡 𝑑𝑡 𝑑𝑑
𝑑𝑥𝑛−1
𝑎𝑛 + 𝑎𝑛−1 𝑥𝑛−1 + ⋯ + 𝑎2 𝑥2 + 𝑎1 𝑥1 + 𝑎0 𝑥 = 𝑘𝑘
𝑑𝑑
𝑎𝑛−1 𝑎𝑛−2 𝑎0
− − ⋯ − 𝑘
𝑥𝑛−1 𝑎𝑛 𝑎𝑛 𝑎𝑛 𝑥𝑛−1
𝑑 𝑥𝑛−2 𝑥 𝑎𝑛
= 1 0 ⋯ 0 𝑛−2
+ 0 𝑢
𝑑𝑑 ⋮ 0 1 ⋯ 0 ⋮
𝑥 ⋮ ⋮ ⋱ ⋮ 𝑥 ⋮
0 0 ⋯ 0 0
State space model finding the output
𝑑𝑛 𝑥 𝑑 𝑛−1 𝑥 𝑑2𝑥 𝑑𝑑
𝑎𝑛 𝑛 + 𝑎𝑛−1 𝑛−1 + ⋯ + 𝑎2 2 + 𝑎1 + 𝑎0 𝑥 = 𝑘𝑘
𝑑𝑡 𝑑𝑡 𝑑𝑡 𝑑𝑑
𝑎𝑛−1 𝑎𝑛−2 𝑎0
− − ⋯ − 𝑘
𝑥𝑛−1 𝑎𝑛 𝑎𝑛 𝑎𝑛 𝑥𝑛−1
𝑑 𝑥𝑛−2 𝑥 𝑎𝑛
= 1 0 ⋯ 0 𝑛−2
+ 0 𝑢
𝑑𝑑 ⋮ 0 1 ⋯ 0 ⋮
𝑥 ⋮ ⋮ ⋱ ⋮ 𝑥 ⋮
0 0 ⋯ 0 0
𝑑𝑛 𝑥 𝑑 𝑛−1 𝑥 𝑑2𝑥 𝑑𝑑
𝑎𝑛 𝑛 + 𝑎𝑛−1 𝑛−1 + ⋯ + 𝑎2 2 + 𝑎1 + 𝑎0 𝑥 = 𝑘𝑘
𝑑𝑡 𝑑𝑡 𝑑𝑡 𝑑𝑑
𝑎𝑛−1 𝑎𝑛−2 𝑎0
− − ⋯ − 𝑘
𝑥𝑛−1 𝑎𝑛 𝑎𝑛 𝑎𝑛 𝑥𝑛−1
𝑑 𝑥𝑛−2 𝑥 𝑎𝑛
= 1 0 ⋯ 0 𝑛−2
+ 0 𝑢
𝑑𝑑 ⋮ 0 1 ⋯ 0 ⋮
𝑥 ⋮ ⋮ ⋱ ⋮ 𝑥 ⋮
0 0 ⋯ 0 0
Values of interest
• In this case, an obvious value of interest is the state x.
• This is the last value in the ‘state vector z’.
Hence : 𝑥𝑛−1
𝑥𝑛−2
𝑥= 0 0 ⋯ 0 1 = 𝐶𝐶
⋮
𝑥
C
z
• If we were interested in the first derivative, this can equally
be determined
𝑥𝑛−1
𝑑𝑑 ⋮
= 𝑥1 = 0 0 ⋯ 1 0 = 𝐶𝐶
𝑑𝑑 𝑥1
𝑥
Values of interest - outputs
If we were interested in the state x and the derivative, we can
give the matrix C two rows and define an output vector
𝑥𝑛−1
𝑥 0 0 ⋯ 0 1 ⋮
𝑦= 𝑥 = = 𝐶𝐶
1 0 0 ⋯ 1 0 𝑥 1
𝑥
𝑥̇ = 𝐴𝐴 + 𝐵𝐵; 𝑦 = 𝐶𝐶 + 𝐷𝐷
𝑑𝑑
𝑑𝑑 = − 𝐵⁄𝑀 − 𝑘 ⁄𝑀 𝑣 1⁄𝑀
+ 𝑓
𝑑𝑑 1 0 𝑥 0
𝑑𝑑
𝑣 1 0 𝑣
The output is = = 𝐶𝐶
𝑥 0 1 𝑥
State Variable to Transfer Function
• If a dynamic system is given is a state variable representation, the
transfer function from any state variable or output variable, to
any input variable can be determined.
• Assume the state initial conditions are zero 𝑥0 = 0
Known :
𝑥̇ (𝑡) = 𝐴𝐴 𝑡 + 𝐵𝐵(𝑡)
𝑦 𝑡 = 𝐶𝐶 𝑡 + 𝐷𝐷(𝑡)
State Variable to Transfer Function
• Taking Laplace transform (with zero initial conditions)
ℒ 𝑥̇ 𝑡 = ℒ 𝐴𝑥 𝑡 + ℒ 𝐵𝐵 𝑡
ℒ𝑦 𝑡 = ℒ 𝐶𝑥 𝑡 + ℒ 𝐷𝐷 𝑡
𝑆𝑆 𝑠 = 𝐴𝐴 𝑠 + 𝐵𝐵(𝑠)
𝑌 𝑠 = 𝐶𝐶 𝑠 + 𝐷𝐷(𝑠)
𝑋 𝑠 𝑆𝑆 − 𝐴 = 𝐵𝐵(𝑠)
State Variable to Transfer Function
−1
• Pre – multiplying both sides by 𝑆𝑆 − 𝐴
𝑋 𝑠 = 𝑆𝑆 − 𝐴 −1 𝐵𝐵(𝑠)
𝑌 𝑠 = 𝐶𝐶 𝑠 + 𝐷𝐷(𝑠)
−1 𝐵𝐵
𝑌 𝑠 = 𝐶 𝑆𝑆 − 𝐴 𝑠 + 𝐷𝐷(𝑠)
−1 𝐵
𝑌 𝑠 = 𝐶 𝑆𝑆 − 𝐴 +𝐷 𝑈 𝑠
𝑌 𝑠 −1 𝐵
𝐺 𝑠 = = 𝐶 𝑆𝑆 − 𝐴 +𝐷
𝑈 𝑠
31
REMARK
−1
𝑌 = 𝐶 𝑠𝑠 − 𝐴 𝐵 + 𝐷 𝑈 ⇒ 𝑝𝑝𝑝𝑝𝑝 ≡ 𝑠𝑠 − 𝐴 = 0
𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒 ≡ 𝜆Ι − 𝐴 = 0
Example 3
• State space model
𝑥̇ 1 𝑥1
0 1 𝑥1 0 𝑦= 1 0 𝑥 + 0𝑈
𝑥̇ 2 = 𝑥 + [𝑈] 2
−2 −3 2 1
−1
𝐺 𝑠 = 𝐶 𝑆𝑆 − 𝐴 𝐵+𝐷
−1
𝑠 0 0 1 0
= 1 0 − + 0
0 𝑠 −2 −3 1
−1
𝑠 −1 0
= 1 0
2 𝑠+3 1
33
Example 3
• Note: Recall that if we have
𝑎 𝑏 −1 1 𝑑 −𝑏
𝐸= , than 𝐸 =
𝑐 𝑑 det(𝐸) −𝑐 𝑎
hence:
1 𝑠+3 1 0
= 1 0
𝑠 𝑠 + 3 + 2 −2 𝑠 1
1 1
= 2 1 0
𝑠 + 3𝑠 + 2 𝑠
1
𝑠 2 + 3𝑠 + 2 34
MATLAB example
A=[1 3; -2 5]
B=[2 ; -1]
C=[1 1]
D=0
[n,d]=ss2tf(A,B,C,D,1)
n =
0 1.0000 -16.0000
d =
𝑠 − 16
1 -6 11 𝐺= 2
𝑠 − 6𝑠 + 11
MATLAB example
A=[1 3 2; 0 -2 5; 1 -0.3 2]
B=[2 ; -1; 0]
C=[1 0 5]
D=0
[n,d]=ss2tf(A,B,C,D,1)
2𝑠 2 + 8.5𝑠 + 5.1
𝐺= 3
𝑠 − 𝑠 2 − 4.5𝑠 − 16.5
Conversion from a transfer function
𝑘
𝑋(𝑠) = 𝑛 𝑛−1
𝑈(𝑠)�
𝑠 + 𝑎𝑛−1 𝑠 + ⋯ + 𝑎1 𝑠 + 𝑎0
𝑑𝑛 𝑥 𝑑 𝑛−1 𝑥 𝑑2𝑥 𝑑𝑑
𝑘𝑘 = 𝑛 + 𝑎𝑛−1 𝑛−1 + ⋯ + 𝑎2 2 + 𝑎1 + 𝑎0 𝑥
𝑑𝑡 𝑑𝑡 𝑑𝑡 𝑑𝑑
State space model
Use the n equations to form a state space model with n states.
𝑑𝑥𝑛−2 𝑑𝑥1 𝑑𝑑
𝑥𝑛−1 = ; 𝑥2 = ; 𝑥1 =
𝑑𝑑 𝑑𝑑 𝑑𝑑
𝑑𝑥𝑛−1
𝑎𝑛 + 𝑎𝑛−1 𝑥𝑛−1 + ⋯ + 𝑎2 𝑥2 + 𝑎1 𝑥1 + 𝑎0 𝑥 = 𝑘𝑘
𝑑𝑑
𝑑𝑛 𝑥 𝑑 𝑛−1 𝑥 𝑑2𝑥 𝑑𝑑
𝑘𝑘 = 𝑛 + 𝑎𝑛−1 𝑛−1 + ⋯ + 𝑎2 2 + 𝑎1 + 𝑎0 𝑥
𝑑𝑡 𝑑𝑡 𝑑𝑡 𝑑𝑑
𝑘
𝑋(𝑠) = 𝑛 𝑛−1
𝑈(𝑠)�
𝑠 + 𝑎𝑛−1 𝑠 + ⋯ + 𝑎1 𝑠 + 𝑎0
Example
Find a control canonical form for the following
4
𝑋(𝑠) = 𝑈(𝑠)
𝑠3 + 2𝑠 2 +𝑠+3
𝑑 0 1 0 0 𝑥
𝑧 = 0 0 1 𝑧 + 0 𝑢; 𝑧 = 𝑥̇
𝑑𝑑 𝑥̈
−3 −1 −2 4
𝑥= 1 0 0𝑧
Example
Find the state space model for the following
𝑋(𝑠)
𝑋1 (𝑠)
𝑊(𝑠) = 0 1 0 ⋯
⋮
𝑋𝑛−1 (𝑠)
𝑠
= 𝑛
𝑠 + 𝑎𝑛−1 𝑠 𝑛−1 + ⋯ + 𝑎1 𝑠 + 𝑎0
Example
Find the state space model for the following
𝑋(𝑠)
𝑋1 (𝑠) 𝑠𝑟
⋮ = 𝑛
𝑊(𝑠) = 0 0 ⋯ 1 ⋯ 0 𝑠 + 𝑎𝑛−1 𝑠 𝑛−1 + ⋯ + 𝑎1 𝑠 + 𝑎0
𝑋𝑟 (𝑠)
⋮
𝑋𝑛−1 (𝑠)
Example
Find the control canonical form for the following
4𝑠
𝑋(𝑠) = 3 𝑈(𝑠) NOTE: Place 4 in the C
2
𝑠 + 2𝑠 + 𝑠 + 3 matrix instead of B
𝑑 0 1 0 0 𝑥
𝑧 = 0 0 1 𝑧 + 0 𝑢; 𝑧 = 𝑥̇
𝑑𝑑 𝑥̈
−3 −1 −2 1
6𝑠 2 + 4𝑠 + 2
𝑌(𝑠) = 4 3 2
𝑈(𝑠)
𝑠 − 𝑠 + 2𝑠 + 𝑠 + 3
0 1 0 0 0
𝑑 0 0 1 0 0
[𝑧] = 𝑧+ 𝑢; 𝑦 = 2 4 6 0𝑧
𝑑𝑑 0 0 0 1 0
−3 −1 −2 1 1
NOTE: The only change is to the C matrix which has all numerator
coefficients!
Example
Find control canonical form for the following
𝑏𝑛−1 𝑠 𝑛−1 + ⋯ + 𝑏1 𝑠 + 𝑏0
𝑌(𝑠) = 𝑛 𝑛−1 2
𝑈(𝑠)
𝑠 + 𝑎𝑛−1 𝑠 + ⋯ + 𝑎2 𝑠 + 𝑎1 𝑠 + 𝑎0
0 1 0 ⋯ 0 0
𝑑 0 0 1 ⋯ 0 0
[𝑧] = 𝑧+ 𝑢
𝑑𝑑 ⋮ ⋮ ⋯ ⋱ ⋮ ⋮
−𝑎0 −𝑎1 −𝑎2 ⋯ −𝑎𝑛−1 1
A B
𝑏𝑛−1 𝑠 𝑛−1 + ⋯ + 𝑏1 𝑠 + 𝑏0
𝐺= 𝑛
𝑠 + 𝑎𝑛−1 𝑠 𝑛−1 + ⋯ + 𝑎2 𝑠 2 + 𝑎1 𝑠 + 𝑎0
𝑏𝑛−1 𝑠 𝑛−1 + ⋯ + 𝑏1 𝑠 + 𝑏0
𝐺=
𝑠 + 𝑝1 )(𝑠 + 𝑝2 ) ⋯ (𝑠 + 𝑝𝑛
𝑅1 𝑅2 𝑅𝑛
𝐺= + + ⋯+
𝑠 + 𝑝1 𝑠 + 𝑝2 𝑠 + 𝑝𝑛
State-space from partial fraction
Define a separate, independent state for each partial fraction term.
𝑅1 𝑅2 𝑅𝑛
𝐺= + + ⋯+
𝑠 + 𝑝1 𝑠 + 𝑝2 𝑠 + 𝑝𝑛
𝑑𝑥1 𝑑𝑥2
= −𝑝1 𝑥1 + 𝑢; = −𝑝2 𝑥2 + 𝑢; ⋯
𝑑𝑑 𝑑𝑑
𝑦 = 𝑅1 𝑥1 + 𝑅2 𝑥2 + ⋯
Example state space model
𝑅1 𝑅2 𝑅𝑛
By inspection 𝐺= + + ⋯+
𝑠 + 𝑝1 𝑠 + 𝑝2 𝑠 + 𝑝𝑛
𝑥1 −𝑝1 0 ⋯ 0 𝑥1 1
𝑑 𝑥2 0 −𝑝2 ⋯ 0 𝑥2 1
⋮ = ⋮ + 𝑢
𝑑𝑑 ⋮ ⋮ ⋱ ⋮ 1
𝑥𝑛 0 0 ⋯ −𝑝𝑛 𝑥𝑛 1
𝑦 = [𝑅1 𝑅2 ⋯ 𝑅𝑛 ]𝑧
Example
Find a state space model for the following.
3𝑠 + 1 3𝑠 + 1
𝐺= 3 𝐺=
𝑠 + 6𝑠 2 + 11𝑠 + 6 𝑠 + 1)(𝑠 + 2)(𝑠 + 3
−1 5 −4
𝐺= + +
𝑠+1 𝑠+2 𝑠+3
𝑥1 −1 0 0 1
𝑑
𝑥2 = 0 −2 0 1 𝑢; 𝑦 = [−1 5 −4]𝑧
𝑑𝑑 𝑥
3 0 0 −3 1
Repeated roots
Where a partial fraction has repeated roosts a slightly modified,
so called Jordan form, is required.
𝑅2 𝑅1
𝐺= 2
+
𝑠+𝑎 𝑠+𝑎
𝑅3 𝑅2 𝑅1
𝐻= 3
+ 2
+
𝑠+𝑎 𝑠+𝑎 𝑠+𝑎
State space for repeated poles
𝑑 𝑥1 −𝑎 1 0
= 𝑢; 𝑦 = 𝑅1 𝑅2 𝑧
𝑑𝑑 𝑥2 0 −𝑎 1
𝑠+𝑎 1 0 1
−1 𝑠+𝑎 2
𝑠𝑠 − 𝐴 −1 𝐵 =
𝑠+𝑎 −1
𝐵 = 0 𝑠+𝑎 1 =
0 𝑠+𝑎 𝑠+𝑎 2 1
𝑠+𝑎
−1 𝐵
𝑅1 𝑅2
𝐶 𝑠𝑠 − 𝐴 = 2
+
𝑠+𝑎 𝑠+𝑎
State space form for repeated poles
𝑥1 −𝑎 1 0 𝑥1 0
𝑑
𝑥2 = 0 −𝑎 1 𝑥2 + 0 𝑢; 𝑦 = [𝑅1 𝑅2 𝑅3 ]𝑧
𝑑𝑑 𝑥
3 0 0 −𝑎 𝑥3 1
−1
−𝑎 1 0
𝑠𝑠 − 𝐴 −1 𝐵 = 0 −𝑎 1 𝐵
0 0 −𝑎 1
𝑠+𝑎 3
2
𝑠+𝑎 𝑠+𝑎 1 0 1
0 𝑠+𝑎 2 𝑠+𝑎 0 =
𝑠+𝑎 2
0 0 𝑠+𝑎 2 1 1
= 3
𝑠+𝑎 𝑠+𝑎
State space form for repeated poles
−1 𝐵
𝑅1 𝑅2 𝑅3
𝐶 𝑠𝑠 − 𝐴 = 3
+ 2
+
𝑠+𝑎 𝑠+𝑎 𝑠+𝑎
Example
Find a diagonal / Jordan canonical form for the following
4𝑠 + 2
𝑋(𝑠) = 3 2
𝑈(𝑠)
𝑠 + 4𝑠 + 5𝑠 + 2
6 −2 −6
𝐺(𝑠) = 2
+ +
𝑠+1 𝑠+1 𝑠+2
𝑑 −1 1 0 0
𝑧 = 0 −1 0 𝑧 + 1 𝑢; 𝑥 = [6 −2 −6]𝑧
𝑑𝑑
0 0 −2 1
Example
Given the following system in the figure below.
(a) Draw the free body diagram and apply D'Alembert's law to write
a modeling equation for the system.
(b) Find the state – variable model for the system
(c) For the system found in (b) , write the state-variable model in
the standard form, i.e state space form 𝒙̇ 𝒕 = 𝑨𝑨 𝒕 + 𝑩𝑩(𝒕)
𝒚 𝒕 = 𝑪𝑪 𝒕 + 𝑫𝑫(𝒕)
60
Example 2
𝐵 𝑥̇ 2 − 𝑥̇ 1 + 𝑘2 𝑥2 − 𝑥1 − 𝑀1 𝑥̈ 1 − 𝑘1 𝑥1 = 0 (1)
𝑓𝑎 𝑡 − 𝑀2 𝑥̈ 2 − 𝐵 𝑥̇ 2 − 𝑥̇ 1 − 𝑘2 𝑥2 − 𝑥1 = 0 (2)
• Rearranging, we have
1
𝑣̇ 1 = − 𝑘1 + 𝑘2 𝑥1 − 𝐵𝑣1 + 𝑘2 𝑥2 + 𝐵𝑣2
𝑀
𝑥̇ 2 = 𝑣2
1
𝑣̇ 2 = [𝑘2 𝑥1 + 𝐵𝑣1 − 𝑘2 + 𝑘3 𝑥2 − 𝐵𝑣2 + 𝑓𝑎 (𝑡)]
𝑀
62
Example 2
𝑥̇ 1 = 0𝑥1 + 0𝑥2 + 1𝑣1 + 0𝑣2 + 0𝑢1
1
𝑣̇ 1 = (𝑘1 + 𝑘2 )𝑥1 + 𝑘𝑘2 + −𝐵𝐵1 + 𝐵𝐵2 + 0𝑢1
𝑀1
1
𝑣̇ 2 = 𝑘2 𝑥1 − 𝑘2 + 𝑘3 𝑥2 +𝐵𝐵1 −𝐵𝐵2 +1𝑢2
𝑀2
63
Example 2
0 0 1 0
𝑥̇ 1 1 𝑥1
(𝑘1 + 𝑘2 ) 𝑘2 −𝐵 𝐵 𝑥2 0
𝑣̇ 1 𝑀1
𝑥̇ 2
=
0 0 0 1 𝑣1 + 0
1
0
𝑣̇ 2 𝑣2
𝑘2 1
𝑀2 − 𝑘2 + 𝑘3 𝐵 −𝐵
64
65